Efficacy and safety of milk thistle preventive treatment of anti-tuberculosis drug-induced liver injury: A protocol for systematic review and meta-analysis. Issue 52 (24th December 2020) - Shi, Zhipeng; Wu, Jing; Yang, Qiang; Xia, Hong; Deng, Min; Yang, Yuxia
Abstract: Background: Tuberculosis is an infectious disease caused by mycobacterium tuberculosis. It may occur in multiple parts and organs of the patients body, and the lung is the most common. It is a major health threat worldwide. Hepatotoxicity is a common adverse reaction of commonly used clinical anti-tuberculosis drugs, as well as one of the important factors leading to poor prognosis of tuberculosis. Milk thistle is a traditional Chinese medicine extract derived from the mature fruit of Silybum marianum. Clinical practice shows that milk thistle has a good anti-liver injury effect and can be used to prevent anti-tuberculosis drug-induced liver injury. However, there is a lack of evidence-based medicine. The research carried out in this protocol is to systematically evaluate the efficacy and safety of milk thistle preventive treatment of anti-tuberculosis drug-induced liver injury, and to improve the evidence-based basis for clinical application of milk thistle in the preventive treatment of anti-tuberculosis drug-induced liver injury. Method: Computer search of English databases (PubMed, the Cochrane Library, Embase, Web of Science) and Chinese databases (CNKI, VIP, Wanfang, China Biology Medicine disc (CBMdisc)) was performed. From the establishment of database to October 2020, 2 researchers independently extracted and evaluated the data included in the randomized controlled clinical research of milk thistle preventive treatment of anti-tuberculosis drug-induced liver injury, and used RevMan5.3 software to conduct a meta-analysis of the included literature. Result: In this research, the efficacy and safety of milk thistle preventive treatment of anti-tuberculosis drug-induced liver injury were evaluated by indicators such as the incidence of liver injury, bilirubin levels, and liver enzyme levels. Conclusion: In this research, reliable evidence-based evidence for the clinical application of milk thistle in the preventive treatment of anti-tuberculosis drug-induced liver injury was provided. OSF Registration number: DOI: 10.17605/OSF.IO/VC3RM.